Dampak Biaya Produksi, Biaya Operasional, Biaya Keuangan dan Biaya Pajak terhadap Laba Bersih Perusahaan: Studi Empiris pada Perusahaan Manufaktur Sektor Barang Konsumsi Sub Sektor Kosmetik dan Kebutuhan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Periode 2020 – 2024 - Siti Nurfia; Rismawandi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the effect of production costs, operational costs, financial costs, and tax costs on the net profit of manufacturing companies in the consumer goods sector, specifically the cosmetics and household needs sub-sectors, listed on the Indonesia Stock Exchange for the 2020-2024 period. The sample in this study consists of 17 companies listed on the Indonesia Stock Exchange during this period. Data was obtained from the companies' financial reports and then processed using Microsoft Excel 2018 and SPSS version 25 software. The research method used is multiple linear regression. The results of this study show that the production cost variable, operational cost variable, financial cost variable, and tax cost variable all have a significant effect on the company's net profit. The production cost variable has a significant impact on the company's net profit, as do the operational costs, financial costs, and tax costs, which all influence the net profit significantly. These findings emphasize that effective management of various costs incurred by the company can increase the net profit, which in turn influences the company's financial performance. Therefore, companies need to focus on managing these costs to achieve optimal profit. This study provides important insights for company management in making decisions regarding cost management to improve financial performance and competitiveness in the market.